The The Effect of Acetobacter xylinum Starter in Waste Liquid Pineapple Peel on the Properties of Nata de Pina - Kiki Nurtjahtja (Talenta Publisher, 2020)
Abstract. Fresh pineapple waste consisted of saccharides, water, protein, lipid, vitamin and minerals that can be used by beneficiary microorganisms for production another food products. The aim of this study was to investigate physical properties nata de pina made from waste liquid pineapple peel using various starter concentrations and length of fermentation of Acetobacter xylinum. The starter used were 20, 30 and 40% ml. Each 200 mL fresh waste containing the starter was incubated for 14, 21 and 28 days at 29°C. Nata properties such as yield, thickness, fibre and water content were determined. Results showed starter concentration and length of fermentation affect and significantly (P<0.05) different on nata thickness, yield and fiber content. The highest yield (35,75%), thickness (24.6 mm) and fibre content (4.43%) occurred at 40% starter after 28 days of fermentation. However, the optimum nata thickness occurred at 21 days. There is no significantly different (P<0.05) at nata moisture on starter concentration and length of fermentation. In conclusion, waste liquid pineapple peel is potential as a raw material source for making nata de pina with starter Acetobacter xylinum.